2014
DOI: 10.1038/nature13116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of nitrate uptake by the plant nitrate transporter NRT1.1

Abstract: SummaryThe NRT1/PTR family of proton-coupled transporters are responsible for nitrogen assimilation in eukaryotes and bacteria through the uptake of peptides. However, in the majority of plant species members of this family have evolved to transport nitrate as well as additional secondary metabolites and hormones. In response to falling nitrate levels, NRT1.1 is phosphorylated on an intracellular threonine that switches the transporter from a low to high affinity state. Here we present both the apo and nitrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
289
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(317 citation statements)
references
References 56 publications
11
289
0
3
Order By: Relevance
“…In the estimation of the p, which is expressed as a fraction rather than a true density, we assumed a transporter opening (s) of 1 nm. This value appears to be close to the opening of a phosphate transporter (Huang et al, 2003;Pedersen et al, 2013), while a value closer to 10 nm was reported for a nitrate transporter (Parker and Newstead, 2014). We note, that the p estimates are affected by the actual choice of s. For example, the p estimates (x-axis in Figure 1) becomes 10 times higher if s is set equal to 10 instead of 1 nm.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the estimation of the p, which is expressed as a fraction rather than a true density, we assumed a transporter opening (s) of 1 nm. This value appears to be close to the opening of a phosphate transporter (Huang et al, 2003;Pedersen et al, 2013), while a value closer to 10 nm was reported for a nitrate transporter (Parker and Newstead, 2014). We note, that the p estimates are affected by the actual choice of s. For example, the p estimates (x-axis in Figure 1) becomes 10 times higher if s is set equal to 10 instead of 1 nm.…”
Section: Discussionmentioning
confidence: 87%
“…where s is the radius of the effective catch area of an uptake site (Aksnes and Egge, 1991) which can be taken as the radius of the opening of a transporter (Parker and Newstead, 2014). The transporter density (p), is the total catch area of all uptake sites divided by the cell surface, i.e., p = nπs 2 /(4πr 2 ).…”
Section: Methods Theoretical Model For the Uptake Affinitymentioning
confidence: 99%
“…The substrate specificity of NRT1/PTR transporters is mainly determined by the specific side chains that line the aqueous pocket at the center of the membrane (Parker and Newstead, 2014;Sun et al, 2014;Yan, 2015). However, how plant NRT1/PTR transporters are able to recognize and transport diverse substrates remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Since the cytoplasmic K + concentrations in root parenchyma cells are over dozens of millimolars, NRT1.5 should be a low-affinity H + /K + antiporter. According to the crystal structure of NRT1.1, the "EXXER" motif (containing three conserved residues) on TMH1 together with the conserved residue Lys-164 on TMH4 is responsible for proton coupling (Doki et al, 2013;Parker and Newstead, 2014;Sun et al, 2014). These four charged residues are highly conserved in most Arabidopsis NRT1 members.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, some PHT1 members could present a dual affinity, a view put forth in this study for Arabidopsis. A characteristic already identified for other transporters such as the K Cup1/Arabidopsis K + Transporter1 (Fu and Luan, 1998) and the nitrate NRT1;1 (Parker and Newstead, 2014;Sun et al, 2014). The posttranslational modifications for PHT1 involved in such mechanism remain to be identified.…”
Section: Dual Affinity For Pi Uptake Appears Conserved In the Differementioning
confidence: 99%